2022
DOI: 10.1186/s12884-022-04423-6
|View full text |Cite|
|
Sign up to set email alerts
|

Expression profiles and functions of ferroptosis-related genes in the placental tissue samples of early- and late-onset preeclampsia patients

Abstract: Background The accumulation of reactive oxygen species (ROS) resulting from upregulated levels of oxidative stress is commonly implicated in preeclampsia (PE). Ferroptosis is a novel form of iron-dependent cell death instigated by lipid peroxidation that likely plays an important role in PE pathogenesis. This study aimed to investigate the expression profiles and functions of ferroptosis-related genes (FRGs) in early-onset preeclampsia (EOPE) and late-onset preeclampsia (LOPE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that preeclampsia was considered to be associated with high iron status and ferroptosis. Placenta [28,29] and different cell lineages at the maternal-fetal interface, [30] including trophoblasts, dendritic cells, stromal fibroblasts, and decidual cells are proved to have different modes of intracellular iron regulation and distinctive sensitivities to ferroptosis. However, many ferroptosis genes have yet to be characterized, and ferroptosis-related genes in STB-EVs are not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that preeclampsia was considered to be associated with high iron status and ferroptosis. Placenta [28,29] and different cell lineages at the maternal-fetal interface, [30] including trophoblasts, dendritic cells, stromal fibroblasts, and decidual cells are proved to have different modes of intracellular iron regulation and distinctive sensitivities to ferroptosis. However, many ferroptosis genes have yet to be characterized, and ferroptosis-related genes in STB-EVs are not explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that miR-30b-5p in PE models can reduce the expression of ferroportin 1 by downregulating Cys2/glutamate antiporter and PAX3, leading to a decrease in GSH and an increase in labile Fe 2+ , therefore promoting the occurrence of ferroptosis in PE patients [ 126 ]. The expression of miR-210 was also found to be increased in placenta in PE models, resulting in iron accumulation and autophagosome formation in trophoblast cells and hemosiderin deposition in placental stroma trophoblasts [ 127 ]. Genetic studies have also found that, in PE, the expression levels of genes mainly responsible for iron metabolism ( FTH1 and FTL ) are downregulated, leading to disruption of iron uptake and intracellular storage, thereby promoting cellular ferroptosis [ 128 ].…”
Section: Ferroptosis and Pre-eclampsiamentioning
confidence: 99%
“…Preeclampsia is associated with insufficient trophoblast infiltration and impaired vascular remodeling in spiral arteries [64]. Impaired vascular remodeling in preeclampsia reduces placental perfusion and oxygenation, and increases oxidative stress with ROS and toxic lipid peroxides [65]. Free radicals activate monocytes and neutrophils to produce pro-inflammatory cytokines, and further produce ROS through the action of various enzymes and the large amount of ROS produced by oxidative stress can damage the trophoblast cell mitochondrial membrane, permeable transport pore, mitochondrial DNA, and mitochondrial enzymes, which in turn triggers preeclampsia, premature rupture of membrane, etc.…”
Section: Abnormal Placental Vascular Remodelingmentioning
confidence: 99%